Dampak Dampak Covid-19 Terhadap Perubahan Perilaku Belanja Bahan Makanan Online Serta Konsumsi Makanan Laut Masyarakat Surabaya - Hambalah, Febrina; Herman; Kirana, Anggita Fadia (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The COVID-19 pandemic has succeeded in causing panic in people all over the world. Changes in consumer spending behavior globally occur simultaneously, including in Indonesia. The level of consumer awareness to always increase their immunity by consuming fresh food ingredients also encourages online grocery shopping activity. However, amid pandemic situation, there is a dilemma between frugality in order to maintain consumer household stability or maintain the health of each family member. Research on the impact of COVID-19 on changes in online grocery shopping behavior and seafood consumption for the people of Surabaya is expected to answer the question of whether the impact of COVID-19 on changes in online grocery shopping behavior and whether this has an impact on consumer priorities in consuming seafood. The methodology used in this research is qualitative methods with phenomenological approach, namely through in-depth interviews. Respondents of this study are 8 women who are stay-at-home-mother and career women. These 8 women have responsibilities as decision makers in family spending. The results obtained from this study are the upper middle-income households in Surabaya made shift not only to shop offline, but also online during pandemic Covid-19. Most of them have added the number of internet gadgets in their home to participate in Study-From-Home method for their children’s school activity. They bought more health supplements, better food ingredients, and fresh ones to maintain their health conditions during Covid times. The seafood consumptions is perceived as one of the ways to build better immunities, thus some of these households have increasing their seafood buying.